Fused Perovskite Tunnel Structures in Ba5Fe6+xS4+xO8 (0.44≤x≤0.55) with x‐Dependent Two‐Stage Magnetizations. Issue 32 (30th June 2016) - Wright, Taylor; Prots, Yurii; Valldor, Martin
Abstract: Ba5 Fe6+ x S4+ x O8 was synthesized through a solid‐state reaction, and pure powders of nominal compositions x =0.44–0.55 were obtained after being rinsed with water. The crystal structures ( P 4/ mmm, a =10.13, c =4.03 Å) and sample purities were investigated by powder synchrotron X‐ray diffraction and were found to be composed of a tunnel lattice (Ba5 Fe6 S4 O8 ), built from fused perovskite units and the tunnel filling (Fe x S x ). The variable composition, that is, the tunnel filling ( x ), causes partially occupied sites as well as crystallographic split positions. Ba5 Fe6+ x S4+ x O8 ( x =0.525) is semiconducting and all investigated compositions exhibit magnetic ground states that could be described as either semi‐spin‐glass‐like ( x >0.5) or canted antiferromagnetic ( x <0.5). The spin‐glass in x =0.525 exhibits magnetic relaxations that are affected by ageing. Abstract : A flip‐flop tunnel : The new tunnel compound Ba5 Fe6+ x S4+ x O8 (0.44≤ x ≤0.55) exhibits a complex magnetization that is proposed to be a combination of a spin‐flip and ‐flop. The magnetic behavior composition ( x ) was dependent on either canted antiferromagnetic or semi‐spin‐glass‐like properties.